2016
DOI: 10.3390/rs8030200
|View full text |Cite
|
Sign up to set email alerts
|

Change Detection of Submerged Seagrass Biomass in Shallow Coastal Water

Abstract: Satellite remote sensing is an advanced tool used to characterize seagrass biomass and monitor changes in clear to less-turbid waters by analyzing multi-temporal satellite images. Seagrass information was extracted from the multi-temporal satellite datasets following a two-step procedure: (i) retrieval of substrate-leaving radiances; and (ii) estimation of seagrass total aboveground biomass (STAGB). Firstly, the substrate leaving radiances is determined by compensating the water column correction of the pre-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Recently, several change detection approaches (see Table 5) have been applied to seagrass environments for various time scales, considering the change in spatial distribution, coverage, and above-ground biomass in the range of 5–40 years [172,173,174,175]. However, no single technique has emerged as superior across diverse marine environments [10].…”
Section: Background and Methodsmentioning
confidence: 99%
“…Recently, several change detection approaches (see Table 5) have been applied to seagrass environments for various time scales, considering the change in spatial distribution, coverage, and above-ground biomass in the range of 5–40 years [172,173,174,175]. However, no single technique has emerged as superior across diverse marine environments [10].…”
Section: Background and Methodsmentioning
confidence: 99%
“…However, the methods are more diverse than those in Table 1. Change detection algorithms have been used in many applications such as arid environment monitoring [100], submerged biomasses in shallow coastal water [101], phragmites australis distribution [102], etc. We will mention some other applications in the following paragraphs.…”
Section: Supervisedmentioning
confidence: 99%
“…Misbari and Hashim [17] used a two-step procedure to estimate seagrass total aboveground biomass (STAGB) using a 2009 Landsat TM and a 2013 Landsat OLI image in Straits of Johor, Malaysia. They demonstrated that Landsat data can be used to accurately estimate submerged STAGB for a multi-year change detection project.…”
Section: Highlights Of Research Articlesmentioning
confidence: 99%